2018
DOI: 10.1021/acs.jpcc.8b04824
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical Properties of Novel Two-Photon Absorbing Dyes: Assessing Their Possible Use for Singlet Oxygen Generation

Abstract: Herein, we assess the nonlinear absorption properties and the photophysical profile and behavior of two recently synthesized polythiophene-based dyes. In particular, using high level state-of-the-art molecular modeling methodologies, we clearly underline the remarkable two-photon absorption (TPA) cross-section. Furthermore, the possible pathways leading to the intersystem crossing and triplet manifold population are investigated by considering the energy difference between the relevant triplet and singlet stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…Also, the nonlinear absorption properties shown by rhodopsin and chlorin based compounds (including Chl‐e6) as well as other dyes, indicate the possible activation of the photosensitizer by two‐photon absorption, hence reducing by the half the required energy to initially populate the photosensitizer excited singlet state, thus opening the way to infrared applications.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the nonlinear absorption properties shown by rhodopsin and chlorin based compounds (including Chl‐e6) as well as other dyes, indicate the possible activation of the photosensitizer by two‐photon absorption, hence reducing by the half the required energy to initially populate the photosensitizer excited singlet state, thus opening the way to infrared applications.…”
Section: Discussionmentioning
confidence: 99%
“…One such example is 2,5-dithienylpyrrole (DTP), which is an excellent electron-donating compound, used by Sharmoukh et al They demonstrated that the modification of DTP could improve its TPA efficiency [104]. Two DTP-based dyes, 1 and 2 (see Figure 3), were designed and synthesized, and their nonlinear absorption properties and photophysical profiles and behaviors were assessed [105]. The D-π-A structure of 1 and 2 [104,106] allows the presence of charge-transfer electronic excited states.…”
Section: Two-photon Absorption Molecules: Small Moleculesmentioning
confidence: 99%
“…30 Absorption spectra at the FC region are obtained either as vertical transitions from the equilibrium geometry, only or taking into account the effects of thermal motions and vibrations by a sampling of the accessible conformational space via a Wigner distribution based on the harmonic vibrational frequencies, following a successful protocol widely used by some of the authors. [31][32][33][34][35][36] The geometries of the first (S A , dark) and the second (S B , bright) excited states have been optimized using TD-DFT at the same level of theory as described above. In addition, the PESs have been explored by means of a bi-dimensional linear interpolation via two generalized coordinates linking the FC region (R FC ) and the two excited states minima R S A and R S B , respectively as reported in eqn (3).…”
Section: Molecular Modelling and Simulationmentioning
confidence: 99%